Prediction of added resistance of ship due to regular head waves - Abdul Ghani, Mohamad Pauzi; Julait, J. (Faculty of Mechanical Engineering, 2008)

(untitled)
This paper presents the added resistance of a 100m Product Tanker due to waves. It includes the study of influence of ship speed and wavelength to the added resistance. This work was carried out by theoretical calculation and model testing in towing tank. The method proposed by Gerritsma & Beukelmen was used in the theoretical calculation technique. This method required ship motion and hydrodynamic coefficients data as input, which was determined using Strip Theory. The model testing was carried out on a 3.382 m model in the towing tank 120m x 4m x 2.5m at the Universiti Teknologi Malaysia’s (UTM) Towing Tank in Skudai, Johore Bahru. Both of the techniques were investigated in three Froude number values, namely 0.21, 0.25 and 0.28. For each Froude number, the study was conducted at wavelength to model length ratio, Lw/Lm between 1.0 and 2.0. The outcomes from both experimental and theoretical calculations were also compared.